2013
DOI: 10.1063/1.4809922
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controllable biaxial strain on the Raman spectra of monolayer graphene prepared by chemical vapor deposition

Abstract: Controllable biaxial strain is delivered to monolayer graphene prepared by chemical vapor deposition via applying an electric field to the underlying piezoelectric [Pb(Mg1/3Nb2/3)O3]0.7-[PbTiO3]0.3 substrate. The effects of tunable strain on the Raman spectra of graphene are investigated in reversible and real-time manners. Such strain can result in a blue shift in 2D band of graphene. The calculations based on the Grüneisen parameter identify the actual biaxial strain to graphene, leading to a continuous 2D b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 26 publications
2
35
0
Order By: Relevance
“…Thus, the possibility of a blue shift by the charge doping effect was thought to be less than that by the strain effect. Similar to previous reports on Raman shifts as a result of biaxial strain [29][30][31], the sensitivity of the 2D peak to thermally generated strain (∂ω 2D /∂ω) was approximately double that of the G peak (∂ω G / ∂ω), and the 2D peak shapes did not change. The only difference was that neither peak was linearly shifted.…”
Section: Figuresupporting
confidence: 87%
“…Thus, the possibility of a blue shift by the charge doping effect was thought to be less than that by the strain effect. Similar to previous reports on Raman shifts as a result of biaxial strain [29][30][31], the sensitivity of the 2D peak to thermally generated strain (∂ω 2D /∂ω) was approximately double that of the G peak (∂ω G / ∂ω), and the 2D peak shapes did not change. The only difference was that neither peak was linearly shifted.…”
Section: Figuresupporting
confidence: 87%
“…The recently developed method of electric-field controlled strain has previously been applied to modulate transport, magnetic, and optical behaviors of various material systems24252627. Here, such a strategy can provide us a unique opportunity to in situ modulate the NIR PL of STO:Ni thin film in a real-time and reversible way.…”
Section: Resultsmentioning
confidence: 99%
“…[16][17][18] In this device architecture, local strain was also induced or measured taking advantage of scanning probe techniques. 19,20 Differently, uniform biaxial strain configurations could be induced by taking advantage of piezoelectric effects in the substrate 21 and by using pressure transmitting media. 22 Concerning uniaxial strain, various studies have demonstrated the possibility to anisotropically deform graphene deposited on nonflat substrates, 23 on polydimethylsiloxane (PDMS) 24 or on similar stretchable substrates.…”
mentioning
confidence: 99%